A review on 5S and total productive maintenance and impact of their implementation in industrial organizations - Kareem, Jamal Ahmed Hama (American Scientific Publishers, 2015)
The key purpose of this paper is to show what has been written about 5S and Total Productive Maintenance (TPM), and the benefits that can be achieved by their implementation in the contemporary industrial organizations. The findings of this paper reveal important issues about the impact of the implementation of 5S in TPM projects, thereby toward improved effectiveness of performance of industrial organizations and enhance their financial position and competitively. The literature on the classification of 5S and Total Productive Maintenance (TPM) has so far been very limited. The paper reviews a large number of published materials in this field, along with it presents the overview about the basic concepts and various practices of implementation of the 5S and TPM. It also highlights many aspects which are needed for implementing these two techniques simultaneously in the contemporary manufacturing scenario. Moreover, in this work, the phases of the successful implementation of 5S and TPM have been highlighted for ensuring smooth and effective their implementation in the workplaces, in addition to identify the factors required to correctly implement the 5S and the TPM. Sum up, the paper contains a comprehensive listing of the leading publications and which have come a long way in the area of 5S and TPM, in addition to a set of proposals that have been developed based on the study model after extensive review of literature. Thus, this paper will be largely beneficial to researchers, maintenance professionals and other concerned officials with improving the performance of production process effectiveness in the industrial organizations. © 2015 American Scientific Publishers. All rights reserved.